Prosedur Pelaksanaan Dan Pengumuman Lelang Oleh Kantor Pelayanan Kekayaan Negara Dan Lelang (KPKNL) - Ersa Malida Astriani; Ngadino Ngadino (Notarius, 2022)
AbstractAuction is a method of buying and selling of goods which is carried out by a person or agency authorized by law to carry out an auction, one of which is the Wealth and auction Service Office. The purpose of writing this article is to find out the procedures for the implementation of the auction conducted by KPKNL. The research method used is the normative juridical method. The results of the discussion of this article are that the auction conducted by the KPKNL is divided into 6 stages including the auction preparation stage in the form of submitting an auction application, determining the auction schedule, announcement of auction, and place of auction time, the second stage of auction implementation conducted by auction officials or someone who authorized to carry out the auction, the bid stage, the payment stage, the stage of submitting documents of ownership of goods and the stage of preparing auction minutes. The conclusion of this article is that the auction is carried out by the State Wealth Service Office and the auction is carried out in accordance with PMK No.106 / PMK.06 / 20l3 and PMK No.93 / PMK.06 / 20l0 regarding the Implementation Guidelines for the auction, the implementation of the KPKNL auction is carried out in 6 stages.Keywords: implementation; auction; KPKNLAbstrakLelang merupakan salah satu metode jual-beli barang yang mana dilakukan oleh seseorang atau instansi yang diberi kewenangan oleh Undang-Undang untuk melaksanakan lelang salah satunya yaitu Kantor Pelayanan Kekayaan Dan lelang. Tujuan penulisan artikel ini untuk mengetahui prosedur pelaksanaan lelang yang dilakukan oleh KPKNL. Metode penelitian yang digunakan yaitu metode yuridis normatif. Hasil dari pembahasan artikel ini yaitu lelang yang dilaksanakan oleh KPKNL dibagi menjadi 6 tahap diantaranya tahap persiapan lelang berupa pengajuan permohonan lelang, penetapan jadwal pelaksanaan lelang, pengumuman lelang,dan tempat waktu lelang, tahap kedua tahap pelaksanaan lelang yang dilakukan oleh pejabat lelang atau seseorang yang berwenang untuk melaksanakan lelang, tahap penawaran, tahap pembayaran, tahap penyerahan dokumen kepemilikan barang dan tahap pembuatan risalah lelang. Simpulan dari artikel ini adalah pelaksanaan lelang oleh Kantor Pelayanan Kekayaan Negara dan lelang dilaksanakan sesuai dengan PMK No.l06/PMK.06/20l3 dan PMK No.93/PMK.06/20l0 tentang Petunjuk Pelaksanaan lelang, Pelaksanaan lelang KPKNL dilaksanakan melalui 6 tahap.Kata kunci: pelaksanaan; lelang ; KPKNL